EVALUASI PELAKSANAAN PENGEMBANGAN USAHA AGRIBISNIS DI PEDESAAN (PUAP) DI GAPOKTAN MEKAR MULYO, KELURAHAN GADANG, KOTA MALANG - Nur Ocvanny Amir; Rahmad Pulung Sudibyo (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
PUAP (Rural Agribusiness Program) is one government business for disconnecting poverty chain in rural areas by providing capital business assistance. GAPOKTAN (farmer group association) Mekar Mulyo is one of the capital business assistance receiver, and they also act as a distributor of the capital to its members. Therefore, it needs to evaluate the implementation of PUAP in GAPOKTAN Mekar Mulyo, gadang, Malang. The analysis used in this research was descriptive qualitative referring on instrument of farmer group association capacity assessment in implementing PUAP. The instrument used consisted of data on indicator of input, process, output, outcome, and benefit. The results of this research could be concluded as follows: 1) The Implementation of PUAP program assistance distribution to farmers in GAPOKTAN Mekar Mulyo has been proceed as minister agriculture regulations, so the program reached its target, member of farmer group who worked on agriculture on farm and off farm, 2) In general, the evaluation on the implementation of PUAP program bone by farmers in GAPOKTAN Mekar Mulyo is right on target. There were problems happened outside of the program which did not influence PUAP program activities. It was decrease on the number of farmer caused age and rice field which was converted to non-agricultural land. Therefore, member of farmer group decreased drastically which caused PUAP funds could not gave significant development.